(untitled) (International Journal of Psychiatric Nursing, 2025)
Introduction: The memory demands of nursing students are significantly greater than those of working adults. One of the most frequently mentioned issues among students is the difficulty in retaining large volumes of academic content. Effective and efficient memory is critical for a student’s success. In every work that we do and every form of communication, we rely completely on the memory of past experiences, conversations, information and skills. It is also the most fundamental aspect of the teaching-learning process. In this study, the researcher aimed to determine whether mnemonics and chunking, a popular widely used memorizing technique, can enhance memory among undergraduate nursing students. Aim: This study aimed to evaluate the effectiveness of mnemonics and chunking interventions on the memory of undergraduate nursing students in selected colleges in Punjab. Methods: A quasi-experimental study was conducted with 100 undergraduate nursing students at selected colleges in Punjab. Participants were assigned to either an experimental group or a waitlist control group using a simple random sampling technique. The experimental group received a 1-and-a-half-hour mnemonics and chunking intervention for one day. Measurements were taken at pre-test (day 1), post-test (day 3), follow-up 1 (7 days later), and follow-up 2 (1 month later). A self-structured memory questionnaire was used to assess memory. Data analysis was carried out using descriptive and inferential statistics. Results: There was a significant difference in the mean post-test memory scores between the experimental group (M = 21.80, SD = 5.16) compared to the waitlist control group (M = 15.90, SD = 4.56), p < 0.05. Conclusion: The mnemonics and chunking intervention proved effective in enhancing memory among undergraduate nursing students at selected colleges in Punjab.